Biology and Demography of Helopeltis bradyi Waterhouse (Hemiptera: Miridae) Reared on Cucumbers - Rich Gemilang Simanjuntak; Tri Harjaka; Arman Wijonarko (Universitas Gadjah Mada, 2022)
Helopeltis bradyi is often used as for research and is required in large numbers. The insects were obtained from cacao plants and reared with cucumber fruit in the laboratory. This study aimed to determine the biology and demography of H. bradyi reared on cucumber under laboratory conditions. The demographic parameters observed were net reproduction rate (Ro), gross reproduction rate (GRR), intrinsic growth rate (r), average generation period (T), and population doubling (DT). The results showed that the egg stage lasted for 6.33 ± 0.47 days, the developmental period of the I‒V instar nymph was 2.13 ± 0.34, 2.07 ± 0.25, 2.13 ± 0.34, 2.33 ± 0.47, and 3.20 ± 0.40 days. The lifespan of male imagoes were 32.33 ± 4.92 days, and female imagoes were 24.60 ± 6.64 days. The adult female pre-oviposition period was 2.2 ± 0.40 days and oviposition period of 22.9 ± 4.66 days. H. bradyi has a type III survival curve which indicated high mortality rates during the first instar egg and nymph population. Demographic statistics of H. bradyi on cucumbers fruit are GRR of 296 individuals per generation, Ro of 196 individuals per parent per generation, rate of r of 0.18 individuals per parent per day, T of 29.34 days, and DT of 3.85 days.